Aurophilicity under pressure: a combined crystallographic and in-situ spectroscopic study - O'Connor, Alice E.; Mirzadeh, Nedaossadat; Bhargava, Suresh; Easun, Timothy L.; Schröder, Martin; Blake, Alexander J. (Royal Society of Chemistry, 2016)
High pressure crystallographic studies on [1,4 C6H4{PPh2(AuCl)}2] (1) reveal the largest pressure-induced contraction of an aurophilic interaction observed for any Au(I) complex; Hirshfeld surface analysis and Raman spectroscopy reveal the presence of several types of intermolecular interaction, which play an important role in the behaviour of 1 as a function of pressure.